PERENCANAAN HOTEL BERBINTANG 6 LANTAI DI KABUPATEN CIANJUR - Fazar, Mohammad; Rahayu, Tanjung (Prodi Teknik Sipil Fakultas Teknik Universitas Suryakancana, 2022)
ABSTRACTCianjur is a city in Indonesia that has a tourist destination. This causes many people from outside the city to come for a vacation in Cianjur district. The increasing population is not propotional to the availability of places to stay especially in the south Cianjur area. The solution that is used as an alternative is a place to stay like a hotel. Vertikal building planning must be based on standard provisions applicable in Indonesia. This hotel planning final project uses a reinforced concrete type structure. This design refers to SNI 2847:2013 for structural congcrete, SNI 1726: 2012 for earthquake analysis, and SNI 1727:2013 for loading. The structures reviewed in this design are plates, beams, colums, stairs and beam-column relationships. Building is on seismic design D. The structural system specified is a special moment resisting frame system (SRPMK). Congcrete quality fc’ = 30 MPa, and steel quality fy = 420 MPa. Structural analysis using the ETABS v16 tool. The result of the structural design obtained in this final project are in the form of slab design, staircase design, beam design, and column design. Structural reinforcement includes 130 mm thick floor slabs in X and Y directions D12-300 mm. Ladder using reinforcement plate direction X D13-250 mm, Y direction D13-450mm, and reinforcement plate landing X direction D13-250 mm, Y direction D13-450mm as well as landing beams measuring 250x300 mm with 2D13 base and field reinforcement as well as bearing and field reinforcement 10 – 120 mm. Main beam using a size of 300x550 mm with the main reinforcement on the top focusl 8D22 bottom focus 2D22, top field reinforcement 3D22 bottom field 5D22, torsion reinforcement on each side 2D13, and bearing shear reinforcement 10 – 100 mm field 10 – 120 mm. Child beams using 250x400 mm with staple reinforcement on the top support 3D19 below 2D19, and top field 2D19 bottom field 2D19 and reinforcing bars 10 – 170 mm. The column uses a size of 600x600 mm with an area of 360000 and 24D25 longitudinal reinforcement and stirrup reinforcement 10- 180 mm Keywords : structural design, earthquake analysis, SRPMK, ETABS, floor slabs, landing, stairs, child beams, main beams, columns. ABSTRAK Cianjur merupakan kota di Indonesia yang mempunyai destimasi wisata. Hal ini menyebabkan banyak masyarakat dari luar kota datang untuk berlibur di Kabupaten Cianjur. Meningkatnya populasi tidak sebanding dengan ketersediaan tempat menginap khususnya di daerah Cianjur Selatan. Solusi yang dijadikan salah satu alternatif adalah tempat menginap seperti hotel. Perencanaan bangunan vertikal harus berdasarkan ketetapan standar yang berlaku di Indonesia. Tugas akhir perancangan hotel ini menggunakan struktur jenis beton bertulang. Perancangan ini mengacu pada peraturan SNI 2847:2013 untuk beton struktural, SNI 1726 : 2012 untuk analisis gempa dan SNI 1727:2013 untuk pembebanan. Struktur yang ditinjau pada perancangan ini adalah pelat, balok , kolom, tangga, dan hubungan balok kolom. Bangunan berada pada desain seismik D. Sistem struktur yang diterapkan adalah Sistem Rangka Pemikul Momen Khusus (SRPMK). Mutu beton fc’ = 30 MPa, dan mutu baja tulangan fy = 420 MPa. Analisis struktur menggunakan program bantu ETABS. Hasil perancangan struktur yang diperoleh pada tugas akhir ini berupa perancangan pelat, perancangan tangga, perancangan balok, dan perancangan kolom. Penulangan struktur meliputi pelat lantai tebal 130 mm dengan arah X dan Y D12 – 300 mm. Tangga menggunakan penulangan tumpuan pelat arah X D13 - 250 mm, arah Y D13 – 450 mm, dan penulangan pelat bordes arah X D13 – 250 mm, arah Y D13 – 450 mm serta balok bordes ukuran 250 x 300 mm dengan tulangan pokok tumpuan dan lapangan 2D13 serta tulangan geser tumpuan dan lapangan 10 – 120 mm. Balok induk menggunakan ukuran 300 x 550 mm2 dengan tulangan pokok pada tumpuan atas 8D22 tumpuan bawah 2D22,tulangan lapangan atas 3D22 lapangan bawah 5D22 , tulangan torsi tiap sisi 2D13, dan tulangan geser tumpuan 10 – 100 mm lapangan 10 – 120 mm . Balok anak menggunakan ukuran 250 x 400 mm2 dengan tulangan pokok pada tumpuan atas 3D19 bawah 2D19 dan lapangan atas 2D19 lapangan bawah 2D19 serta tulangan sengkang 10 – 170 mm. Kolom menggunakan ukuran 600 x 600 mm2 dengan luas 360000 serta tulangan memanjang 24D25 dan tulangan sengkang 10- 180 mm.